Diagnosis of failure of combustion in the combustion chamber with a thermovision equipment - S. V. Vorobiev; Yu. I. Pavlov (Научный вестник МГТУ ГА, 2016)
The use of thermovision technology to diagnose failure of the combustion flame test tube of the main combustion chamber gas turbine engine is deal with in the article. Join the thermal radiation of the jet of combustion products and the internal elements was carried out using short-wave thermovision system AGA-782 with spectral spectral filters in several ranges from 3.2 to 5.6 microns. Thermovision is mounted on the axis of the flame tube. The output signal was recorded and processed on a computer in real time, allowing monitor the combustion process and the thermal state of the object during the experiment.